Electric-field switching of perpendicularly magnetized multilayers - Shirahata, Yasuhiro; Shiina, Ryota; González, Diego López; Franke, Kévin J A; Wada, Eiji; Itoh, Mitsuru; Pertsev, Nikolay A; van Dijken, Sebastiaan; Taniyama, Tomoyasu (NPG Asia materials, 2015)
Perpendicularly magnetized layers are used widely for high-density information storage in magnetic hard disk drives and nonvolatile magnetic random access memories. Writing and erasing of information in these devices is implemented by magnetization switching in local magnetic fields or via intense pulses of electric current. Improvements in energy efficiency could be obtained when the reorientation of perpendicular magnetization is controlled by an electric field. Here, we report on reversible electric-field-driven out-of-plane to in-plane magnetization switching in Cu/Ni multilayers on ferroelectric BaTiO 3 at room temperature. Fully deterministic magnetic switching in this hybrid material system is based on efficient strain transfer from ferroelastic domains in BaTiO 3 and the high sensitivity of perpendicular magnetic anisotropy in Cu/Ni to electric-field-induced strain modulations. We also demonstrate that the magnetoelectric coupling effect can be used to realize 180° magnetization reversal if the out-of-plane symmetry of magnetic anisotropy is temporarily broken by a small magnetic field. Magnetic memory: electric-field switching for efficient storage An electric-field switching technique can lower the energy required to write and erase data in high-density magnetic storage devices. Perpendicularly magnetic recording is a new technology that aligns magnetic bits into vertical arrangements using specially constructed multilayer films. Normally, magnetic fields or intense bursts of electric currents are needed to modify individual bits. Tomoyasu Taniyama from the Tokyo Institute of Technology and international collaborators have discovered that growing perpendicularly magnetised copper-nickel multilayers on top of ferroelectric BaTiO 3 crystals produces devices responsive to modest electric fields. Laser-based measurements and theoretical analysis revealed that this fast, reversible, and room temperature data switching method was driven by mechanical strain at the metal multilayer-ferroelectric interface. Successful results with films up to 65 nanometers thick indicate that this approach holds promise for practical spintronics applications. Reversible electric-field-driven magnetization switching between perpendicular-to-plane and in-plane orientations in Cu/Ni multilayers on ferroelectric BaTiO 3 is demonstrated at room temperature. Fully deterministic magnetic switching is based on efficient strain transfer from ferroelastic domains in BaTiO 3 and the high sensitivity of perpendicular magnetic anisotropy in Cu/Ni to electric-field-induced strain modulations. The magnetoelectric coupling effect can also be used to realize 180° magnetization reversal if the out-of-plane symmetry of magnetic anisotropy is temporarily broken by a small magnetic field.